Vascular disruption of the talus: Comparison of two approaches for triple arthrodesis - Phinit Phisitkul (2018)
Background: For triple arthrodesis, a single medial incision has been proposed to avoid lateral wound complications and has demonstrated satisfactory fusion rates. This study aimed to compare the disruption to the arterial supply of the talus between the single-medial-incision approach and the 2-incision approach. Methods: The 2 approaches for triple arthrodesis were compared by analyzing the disruption of arterial vasculature in 14 cadaveric specimens in randomized fashion. The arterial disruption was determined using CT angiography before and after surgery combined with analysis from dissection. The area of joint preparation from each technique was also analyzed and compared. Results: The single-medial-incision approach caused a high incidence of damage to the deltoid artery (6 of 7 specimens, 86%) and the artery of the tarsal canal (7 of 7 specimens, 100%). The 2-incision approach resulted in damage to the artery of the tarsal sinus in all specimens (7 of 7 specimens, 100%), but the medial vasculature was spared given the limited dissection required to access the talonavicular joint. Through the single-medial-incision approach the percentage of debridement of the calcaneocuboid joint (36%) was significantly lower than the debridement using the 2-incision approach (85%, P < .01). There was no significant difference in joint preparation of the talonavicular and subtalar joints between the 2 approaches with the number of specimens available. Conclusion: From this cadaveric study, we found that both approaches could result in substantial disruption of the main blood supply to the talus. The single-medial-incision approach consistently disrupted the majority of blood supply to the talar body, while the 2-incision approach caused various degrees of vascular disruption to the talar head and neck. Using the single-medial-incision approach, the calcaneocuboid joint did not show adequate removal of articular cartilage due to difficulty accessing the joint surfaces. Clinical Relevance: Vascular sparing to the talus should be considered when selecting an appropriate operative approach for triple arthrodesis. Although the clinical significance of this cadaveric study is limited, the 2-incision approach appeared to cause less vascular disruption to the talar body while allowing more complete joint preparation. © The Author(s) 2013.